Podcast-Mediated Students Learning English in the Second Grade of Senior High School - Laiya, Rebecca Evelyn; Khasanah, Umul; Sulistiani, Indah; Sudrajat, Didi; M, Miswan (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2022)
Podcasts are one of the well-liked technological advancements to aid language acquisition. Podcasts, which are digital recordings, can be utilized to help students acquire the English language, particularly in speaking and skills. The reconducted was skilled at SMAN to know how to teach speaking and listening skills in high school using podcast media. Researchers used qualitative methods with observation and interview approaches and an interactive model for data analysis. The study results are (1) podcasts are a solution to students' difficulties in learning English as a medium for utilizing technology, (2) podcasts as a medium for learning speaking and listening skills, (3) podcasts can increase student motivation in learning English. So, this researcher draws the conclusion that Podcasts are one of the choices of English learning aids that also allow teachers to use technology in the classroom. It is important to highlight that the aim is not to replace podcasts as a substitute for live teaching. Therefore, it is recommended that when using podcasts, teachers should instruct their students well to maximize their effectiveness.